Unidades fraseológicas do Português em contato com o falar Guajajára (Tupi-Guarani) - Oliveira, Francisca Imaculada Santos (2017)
The main aim of this work is investigate Portuguese phonological units in contact with the Guajajára (Tupi-Guarani), native language of the Cachoeira village indigenous community, with the purpose of contributing to the description of the phraseological units that are spoken in Portuguese by non-native speakers Native speakers of that language. In addition to this general objective, in our research we present other more specific ones: a) To initiate the constitution of a database of Portuguese spoken as a second language; B) Identify phraseological units in Portuguese in the guajajára language; C) To carry out a survey, in phraseological dictionaries and in works on Portuguese speaking words, with the purpose of verifying the dictionalization of the phraseological units collected in the indigenous speech; D) To contribute to the cultural preservation and documentation of the use of Portuguese phraseological units, in the speaking of the guajajáras. To do so, we perform three stages of field research. The research site was the city of Barra do Corda (MA), in the Cana Brava indigenous land, with Indians living in the village Cachoeira. Data were collected locally, through the collection of personal oral narratives, obtained from a sample of 10 informants. The work is justified by the lack of scientific research on Portuguese phraseological units in contact with the indigenous language and the importance of investigating the phraseologies present in the lexicon of Portuguese as a second language. We call ourselves a theoretical-methodological support in Labov (2008); Tarallo (2001) and Calvet (2002); Biderman (2001); Vilela (1979); Rodrigues (1986); Montoro del Arco (2006), Corpas Pastor (1996) and Salah Mejri (2012). With the realization of the research, we believe that we have achieved the objectives we have proposed and will contribute to the description of Portuguese spoken in indigenous areas.